(untitled) (Medical Forum Monthly, 2024)
Objective: To determine the frequency and patterns of fasting lipid profile in patients presenting with polycystic ovarian syndrome in gynecological and endocrine clinics in a tertiary care hospital Study Design: A Cross Sectional Survey Place and Duration of Study: This study was conducted at the Darul Sehat Hospital, Karachi from August 2017 to July 2018. Materials and Methods: This study was conducted on 110 Female patients who were diagnosed as PCOS on the basis of Rotterdam criteria after taking the history according to predesigned proforma and the required investigations. Lipid profile was analyzed using national lipid association and the national cholesterol education program (NCEP) guidelines for lipids. Postmenopausal, pregnant and patients with diabetes and hypothyroidism were excluded from the study. Informed consent was sought from all patients and collected information was analyzed using the SPSS 21 version. Results: In our study dyslipidemia was observed in 96.3% of 110 PCOS patients. The mean age was 25.8+5.9 years and mean BMI was 26+4.6 Kg/m2. About 80% of PCOS patients had low HDL, 73.5 % have high LDL, 31% have high cholesterol, and 12.7 % have high TG levels. Conclusion: In conclusion, dyslipidemia is common in women with PCOS so early detection and prompt treatment of dyslipidemia would definitely improve quality of life and reduce the cardiovascular complications and burden of care.